The implementation of Numbered Heads Together technique in improving speaking ability - Amirullah Amirullah; Potjut Ernawati; Nurul Inayah (Research in English and Education Journal, 2017)
This study is meant to figure out whether the implementation of Numbered Heads Together can improve students’ speaking ability in terms of descriptve text. The writer conducted an experimental research by using one group pretest-posttest. Total sample of students was 20 students and they were chosen by using purposive sampling technique. The instruments used to measure students’ speaking achievement by using oral performance test. There were three meetings for the treatments. The students’ pre-test mean score was 75.40 and posttest 80.70. Each aspect was improved after the treatment, i.e. Vocabulary 16 or (10.0%), fluency 17.6 or (9.50%), pronunciation was17.1 or (4.50%), comprehension 16 or (1.50%), grammar 14 or (1.00%). The writer used 5% (a=0.05) as significant value.  The t-test result, i.e. tvalue (2.34) was higher than ttable  (1.73) suggesting that Ha is accepted. This finding shows that the implementation of Numbered Head Together Technique improved second grade junior high school students’ speaking ability (vocabulary, fluency, pronunciation, comprehension, grammar) in terms to describing people, places or things orally. Therefore, it is suggested that teachers who want to develop their students’ speaking ability use this technique.